Efeito do momento de fotoativação nas propriedades de cimentos resinosos experimentais de dupla ativação com diferentes concentrações de carga - Oliveira, Ana Carla de Assunção (2015)
The reduction of shrinkage stress of resin cements, without loss of their mechanical properties, is essential to longevity of adhesive luting procedures. It has been demonstrated that the delayed light-curing of dual-cured resin cements reduces the shrinkage stress. However, the effects of this postponement on mechanical properties showed are dependent form material composition. Thus, the aim of this study was to evaluate the effect of filler content on properties of dual-cured resin cements light-cured immediately or 5 minutes after their mixing. Two light-curing protocols were additionally evaluated, using a single or 3-point of light-activation. For this purpose, only the cement with 65% of filler was used. Experimental dual-cured resin cements were formulated using a monomeric matrix BisGMA/TEGDMA (1:3 in weight) and filled with 60, 65 or 68% of silanated barium borosilicate glass. The viscosity of experimental cements was measured using a digital viscometer. Bar-shaped specimens (25 x 2 x 2 mm) were confectioned, while the light-curing was performed immediately or 5 minutes after the insertion of cements into the mold (n = 7). Three-point bending test was performed and the values of flexural strength and elastic modulus were measured. The fractured specimens (n = 5) were included into epoxy resin cylinders, polished and the Vickers hardness measurement was performed. Data from viscosity were submitted to one-way ANOVA, while the data from mechanical properties were analyzed by two-way ANOVA. All pair-wise comparison were performed using Tukey’s test (α = 0.05). Specimens that were light-cured at 3 points showed the highest values of flexural strength. Only for light-activation at 1 point, the moment of light-activation affected the elastic modulus (higher for delayed). Cements with 68% of filler showed highest viscosity and those with 60% presented the lowest one. Irrespective of light-curing moment, the cement with 65% of filler presented the highest values of flexural strength and elastic modulus. Addition of 60% of filler resulted in the lowest elastic modulus, while 68% of filler resulted in lowest flexural strength. Regarding the hardness, the cement with 68% of filler showed the highest values, while there was no difference between 60 and 65% of filler. In conclusion, the filler content affects the mechanical properties of cements and this effect is independent form moment of light-curing.